Effects of Parecoxib Sodium Application Combined with Enhanced Recovery After Surgery Nursing on Inflammatory Factors and Knee Joint Function in Elderly Patients After Total Knee Arthroplasty - Deng, Liqiong; Tan, Liping (Frontiers in Surgery, 2022)
Objective: To study the effect of parecoxib sodium (PS) application combined with enhanced recovery after surgery on inflammation and knee joint function in elderly patients after total knee arthroplasty (TKA). Methods: In this prospective cross-sectional study, we recruited 120 elderly patients treated with TKA who were randomly divided into combine group and control group, 60 patients in each group. Patients in the control group received enhanced recovery after surgery and normal saline, and the patients in the combine group received enhanced recovery after surgery and parecoxib analgesia. At different times after surgery, we compared the hemoglobin (Hb), complete white blood cell count (WBC), erythrocyte sedimentation rate (ESR), and serum IL-1β, TNF-α and IL-6, and recovery time for different range of joint motion, and Knee joint function HSS score between two group. Results: On the third and seventh postoperative days, the levels of Hb in the patients of Combine group were all significantly lower than that in control group (P<0.05), while the levels of WBC, ESR, serum IL-1β, TNF-α and IL-6 in the patients of Combine group were all significantly higher than that in control group (P<0.05). Compared with patients in control group, the recovery time for 30, 60, 90 and 120 angles of joint motion in patienst of combine group were all significantly decreased (P<0.05), and the HSS score of patients in combine group were all significantly higher than that in control group on the first, third and 6th postoperative months (P<0.05). Conclusion: Elderly TKA patients who received parecoxib sodium application combined with enhanced recovery after surgery had lower inflammation in peripheral blood 2 weeks after operation and faster postoperative recovery of knee joint function.